Evaluation of Factors of Competitiveness of Light Industries in Regions - Nizamov Aslitdin Badreddinovich; Rahmonov Xurshid Xayriddinovich (European Science Publishing, 2024)
In this article, in order to evaluate the factors of competitiveness of light industries, a questionnaire was conducted among the enterprises that are members of the "Uztoqimachiliksanoat" association and the "Uzbekcharmpoyabzali" association of textile, sewing-knitting and leather industry enterprises of Uzbekistan operating in the Zarafshan region. The questionnaire consisted of 37 questions representing factors grouped into 5 groups and 3 free questions.
Keywords: light industry, vertical control, what kind of tolerance, what kind of tolerance tools, foresight, mainstream.